An FSGO based Electronegativity Scale invoking the Electrophilicity Index. Issue 44 (24th November 2022) - Kumari, Dimple; Saloni,; Tandon, Hiteshi; Labarca, Martín; Chakraborty, Tanmoy
Abstract: Electronegativity is an important chemical construct that plays a pivotal role to explain several chemical, biochemical and physicochemical phenomena. The study of this periodic descriptor is still considered an active domain of research, and a number of scientists are involved to propose different scales of electronegativity based on experimental findings and theoretical concepts. In this study, we have proposed a model to compute atomic electronegativity values of 103 elements based on the Floating Spherical Gaussian Orbital approach invoking the atomic electrophilicity index as a descriptor. The computed electronegativity scale observes the periodic trend and justifies many chemical phenomena. Molecular electronegativity values have also been computed using the computed atomic electronegativity data and utilized to justify the Electronegativity Equalization Principle. In order to validate our proposed model, internuclear bond distances for some molecules have been deduced in terms of our computed atomic electronegativity data. A strong correlation with experimental counterparts proves the efficacy of our proposed model. Abstract : Electronegativity is an important chemical construct which plays a major role in determining physico‐chemical behaviours of atoms and molecules. In this work, a model is proposed for atomic electronegativity within the confinement of FSGO approach keeping electrophilicity as the basis. The FSGO technique is suitable for systems with an even number of electrons and the lowest energy state. It is assumed that each pair of electrons occupies a single spherical Gaussian orbital centre at an arbitrary position in the molecule. The approach is quite simple in terms of mathematical complexity but rigorous to explain chemical properties. The scale of electronegativity presents values for atoms of 103 elements. Proposed atomic electronegativity values nicely observe periodic trend and justify many chemical phenomena. The present works' electronegativities are also compared with some well‐known scales. Electronegativity Equalization Principle is also verified. Further, some simple reactions have been selected and their reactants' and products' total electronegativities have been calculated to verify if they follow "|Δμ| big is good" rule or not. The applicability of our proposed scale has also been tested by calculating internuclear bond distance for some inorganic molecules which yield higher values of correlations. Moreover, the results are in coordination with the van Arkel‐Ketelaar triangle.